Selvskadende adfærd på sociale medier - Vestergaard, Camilla Beck; Jørgensen, Carsten René (Psyke & Logos, 2016)
Traditionally non-suicidal self-injury has been seen as shameful behavior and those suffering from it have concealed it from their surrounding environment. There is a tendency that is growing amongst adolescents with non-suicidal self-injury behavior, in particular adolescent girls, who are now sharing graphic pictures of their non-suicidal self-injuries on social media platforms such as Instagram. This article investigates the psychological mechanisms, which lie behind this phenomenon. This is done within a clinical group of adolescents with non-suicidal self-injury behavior. It is suggested that these social media platforms help the adolescents to create a meaningful identity and to enter into meaningful relations with other like-minded people. It is therefore considered important to understand the social medias and their impact on the adolescents’ process of building their identity and relations with others, when one is dealing with non-suicidal self-injury.